Exploring the Structural Spread of Close-Mindedness as an Epistemic Vice in Indonesia - Arrafi Silitonga, Ferris; Sandi Pratama, Herdito (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2024)
The post-Suharto era in Indonesia, which spans over 26 years and encompasses numerous leadership changes, has been marked by significant democratic challenges. The period is defined by the rise of populism, increasing polarization, and institutional resistance to open discourse. Sensitive discussions regarding the principles and ideologies of the state are often met with reluctance or outright rejection by governmental institutions. These tendencies reflect a deeper structural issue: the intellectual vice of close-mindedness, as examined through the lens of vice epistemology. This paper argues that close-mindedness operates not only at an individual level but also as a systemic issue entrenched within institutional frameworks, creating a feedback loop between political structures and societal attitudes. The paper examines the relationship between institutional resistance and societal polarization, shedding light on how these elements reinforce one another. Additionally, it investigates the cultural and historical factors that have contributed to the perpetuation of close-mindedness as an epistemic vice in Indonesia’s governance and political culture. Left unaddressed, this structural vice threatens to undermine the integrity of Indonesia’s democracy and further deepen societal divisions. In its conclusion, the paper offers practical recommendations to break this cycle, emphasizing the need for fostering intellectual humility, strengthening democratic institutions, and encouraging open and critical public discourse to safeguard the nation’s democratic trajectory.